TANTANGAN PENEGAKAN HUKUM TERHADAP KEJAHATAN SIBER BERBASIS ARTIFICIAL INTELLIGENCE DI INDONESIA - Muhammad Atho’hillah (PT. Habe Cendekia Utama, 2025)
The development of Artificial Intelligence (AI) technology has transformed the cybercrime landscape from manual attacks to automated, adaptive, and difficult-to-detect attacks, increasing the complexity of threats to national security, social stability, and citizens' rights in the digital space. In Indonesia, the legal framework, consisting of the ITE Law, the Criminal Code, and the Personal Data Protection Law, provides a regulatory basis, but it is not fully responsive to new crime modes such as deepfakes, AI-enhanced phishing, and cross-border autonomous attacks. This study aims to analyze the normative, technical, and institutional challenges in law enforcement against AI-based cybercrime, while also formulating directions for strengthening regulations, digital forensic capacity, and AI governance in Indonesia. The method used is qualitative research with a literature review through a review of laws and regulations, decisions, scientific literature, and institutional reports. Content analysis techniques were used to identify legal gaps, technical barriers, and weaknesses in coordination between law enforcement actors. The research findings indicate that there is still a gap in conceptual regulations regarding AIbased cybercrime, limited human resources and digital forensic infrastructure, and institutional fragmentation. Therefore, a more adaptive reconstruction of the cyber legal system is needed, the establishment of adequate forensic tools and high tech crime units, and the strengthening of AI governance based on the principles of transparency, accountability, and human rights protection